Nitrile functionalized silyl ether with dissolved LiTFSI as new electrolyte solvent for lithium-ion batteries. (20th October 2015) - Pohl, Benjamin; Grünebaum, Mariano; Drews, Mathias; Passerini, Stefano; Winter, Martin; Wiemhöfer, Hans‑Dieter
Highlights: A new electrolyte based on a nitrile-silyl ether solvent and LiTFSI as lithium salt was successfully tested. This electrolyte shows higher ionic conductivities as compared to earlier published silicon based solvents. Due to the absence of ether groups, the electrochemical stability is extended to 5.4 V vs. Li/Li + . With LiTFSI, the electrolyte can be cycled up to 4.15 V vs. Li/Li + without causing anodic aluminum dissolution. Abstract: 3-((Trimethylsilyl) oxy) propionitrile is introduced as non-volatile solvent for lithium-ion battery electrolytes using LiTFSI as lithium salt. The thermal and chemical stability of the electrolytes offer an enhanced safety as compared to conventional volatile carbonate electrolytes. In cell tests, the investigated LiTFSI nitrile silyl ether electrolyte shows compatibility with LiFePO4, LiNi0.33 Mn0.33 Co0.33 O2 and graphite active materials.